Improving the capability of decision making high school students through physical practicum activities using HOTV-lab model - E Erlina; A Setiawan; A Suhandi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to get a picture of the improvement of decision-making ability of high school students as the effect of using HOTV-Lab model in Physics practicum activities. The research method used is pre-experiment with design one group pretest-posttest design. The subject of research is 40 students in one of high school in West Bandung. The subjects were chosen by random sampling technique. Instruments used for data collection decision-making ability at the time before and after Physical practicum activities is a test of decision-making ability in the form of essay test. Increased decision-making ability of high school students was analyzed using the concept of normalized average gain scores, <g> formulated by Hake. The results showed that 78% of students had a high increase, 19% of students had moderate increase and 3% had a low increase in decision-making ability. This suggests that the use of the HOTVLab model in Physical practicum activities has a moderate effectiveness in facilitating improved decision-making capabilities.